An exploratory study of the relevance of trans-national global information systems to small and medium enterprises: evidence from Egypt. (19th March 2009) - Samaha, Khaled; Baki, Adam
This paper provides an investigation into the information system (IS) strategy of SMEs in Egypt using questionnaires and case studies to explore if a trans-national global IS can be applied to SMEs in Egypt. Generally, most Egyptian SMEs lack the structure needed to successfully plan an ISS. However, it was evidenced that top management involvement is present at the decision-making stages and throughout implementation and IS planning is undertaken in some way by Egyptian SMEs. The case studies revealed that SMEs operating with a structured hierarchy proved to be far more advanced with regard to information system strategy planning (ISSP). The results of the OLS regression analysis indicated that the higher the involvement of top management in IS decision-making in Egyptian SMEs the more advanced the organisation regarding ISS; organisations that have an IS department and a specific IS budget are more successful in planning and implementing IS strategy; there is a lack of expertise to adequately implement ISS in new companies and in companies from the public sector and finally, the greater the IS budget the greater the outsourcing activities of a firm. A theory of trans-national global IS can therefore be applied to Egyptian SMEs with some modifications due to differing cultures.